Relationship between hepcidin and GDF15 in anemic patients with type 2 diabetes without overt renal impairment. Issue 1 (July 2015) - Hong, Jun Hwa; Choi, Yeon-Kyung; Min, Byong-Keol; Park, Kang Seo; Seong, Kayeon; Lee, In Kyu; Kim, Jung Guk
Highlights: The serum level of GDF15 is highly expressed in patients with T2DM as an inflammatory cytokine. Hepcidin is important protein to induce anemia of chronic disease. The serum level of hepcidin is more increased and associated with risk factor for anemia in anemic patients with T2DM. Hepcidin showed positive correlation to GDF15. Abstract: Aims: Despite the absence of overt renal impairment and decreased erythropoietin (EPO) levels, patients are usually anemic. Hepcidin, which is induced by inflammatory stimuli, plays an important role in anemia in chronic disease. Growth differentiation factor 15 (GDF15) is a putative anti-inflammatory cytokine that is elevated in type 2 diabetes (T2DM). Hence, we investigated the relationship between hepcidin and GDF15 in anemic T2DM patients without overt renal impairment. Methods: Among 1150 patients who visited Kyungpook National University Hospital for T2DM between June 2006 and June 2014, we selected 55 anemic patients without overt renal impairment (serum creatinine <1.5 mg/dL or estimated glomerular filtration rate >60 mL/min/1.73 m 2 ) and other co-morbid diseases, including malignancy, thyroid disease, rheumatic arthritis, liver disease, iron-deficiency anemia and other endocrine disease. We measured anthropometric and metabolic parameters, as well as measured the serum iron, ferritin, interleukin-6 (IL-6), erythropoietin, hepcidin-25 and GDF15 levels. Results: Anemic T2DM patients without overt renal impairment presented a greater inflammatory state, with increased serum hsCRP, ESR and IL-6 levels compared with non-anemic T2DM patients. Both hepcidin and GDF15 levels were increased and showed a positive correlation in anemic T2DM patients. Conclusion: In the absence of overt renal impairment, anemia in T2DM is associated with chronic inflammation, inducing elevation of hepcidin and GDF15 levels independently of the erythropoietin level.